On the C∗ -algebra valued G-metric space related with fixed point theorems - Ozen ¨ Ozer; Saleh Omran (Қарағанды университетінің хабаршысы. Математика сериясы, 2019)
There are many fixed point results in the various kinds of metric spaces such as b - metric spaces, quaternion metric spaces, G-metric spaces, uniform spaces, non - commutative Banach spaces etc. In this work, we consider the one of modern methods as C*-algebra G-metric space with fixed point theory to solve problems above mentioned. We prove the fixed point theorems for a mapping under the contractive conditions in C*-algebra G-metric space. Besides, we establish the not only existence but also uniqueness theorem of fixed point in the such space. Also, we provide several examples to put support behind our main result.